Sprint Acceleration Mechanics: The Major Role of Hamstrings in Horizontal Force Production - Morin, Jean-Benoît; Gimenez, Philippe; Edouard, Pascal; Arnal, Pierrick; Jiménez-Reyes, Pedro; Samozino, Pierre; Brughelli, Matt; Mendiguchia, Jurdan (Frontiers in Physiology, 2015)
Recent literature supports the importance of horizontal ground reaction force (GRF) production for sprint acceleration performance. Modeling and clinical studies have shown that the hip extensors are very likely contributors to sprint acceleration performance. We experimentally tested the role of the hip extensors in horizontal GRF production during short, maximal, treadmill sprint accelerations. Torque capabilities of the knee and hip extensors and flexors were assessed using an isokinetic dynamometer in 14 males familiar with sprint running. Then, during 6-s sprints on an instrumented motorized treadmill, horizontal and vertical GRF were synchronized with electromyographic (EMG) activity of the vastus lateralis, rectus femoris, biceps femoris and gluteus maximus averaged over the first half of support, entire support, entire swing and end-of-swing phases. No significant correlations were found between isokinetic or EMG variables and horizontal GRF. Multiple linear regression analysis showed a significant relationship (P = 0.024) between horizontal GRF and the combination of biceps femoris EMG activity during the end of the swing and the knee flexors eccentric peak torque. In conclusion, subjects who produced the greatest amount of horizontal force were both able to highly activate their hamstring muscles just before ground contact and present high eccentric hamstring peak torque capability.